Study on flow and heat transfer characteristics of phase change synergistic combination finned liquid cooling plate. (November 2022) - Zhang, Furen; Liang, Beibei; He, Yanxiao; Gou, Huan; Zhu, Yilin; Lu, Fu; Xiao, Kang
Abstract: In order to enhance the heat transfer performance of the battery thermal management system, to obtain a more uniform temperature distribution and to achieve the lightweight design requirements, a new liquid cooling plate design approach with primary and secondary combined fins synergistic phase change materials and nanofluid is proposed in this paper. Based on the traditional square fins, 10 new improved fin design options are proposed in this paper. Firstly, the thermal and flow characteristics of the 10 new improved fins are compared and analyzed, and the optimization is carried out. Next, the optimal model is obtained by considering the primary fin size and introducing the secondary fins of the partitioned combination for optimization. Compared to the traditional square fins, the average temperature is reduced by 0.288 °C and the pressure drop is reduced by 1.287 Pa (17.42%). Then, based on the optimal model, the thermal performance of the combined filling method and thickness of PCM is discussed and analyzed for different Reynolds number conditions. The results indicated that the smaller the Reynolds number, the more significant the heat dissipation effect of the filled PCM. The optimal model with PCM filling reduces the mass by 41.4 g (68.86%) compared to the model without PCM, with significant lightweighting effect. Finally, to further improve the thermal performance of the system, different types of nanoparticles with different volume fractions are introduced into the system. Compared to pure water liquid cooling, the Nusselt number can be increased by 9% to 78%, and the heat dissipation effect is significantly improved. Highlights: Based on the traditional directional fins, 10 new and improved fins are proposed. Thermal performance of the system was improved after introduction the secondary fins. A new liquid cooling plate with PCM synergistic combination fins was proposed. The mass of the optimal model after filling the PCM was reduced by 41.4 g (68.86%). Nusselt number of system can be improved by 9% to 78% after introduction nanofluid.